The Development of Economics Education: Focus on Banking Management and Entrepreneurship - Judijanto, Loso; Rimbano, Dheo; Murthada, Murthada; Hendra, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The aim of this research is to identify the development of economic education in Indonesia which focuses on bank management and entrepreneurship, analyze the factors that influence the successful implementation of economic education related to these two fields, and develop recommendations for developing a more effective economic education curriculum to improve financial skills and entrepreneurship among students. The method used in this literature study is library research, which involves collecting data through various library sources such as books, encyclopedias, documents and scientific journals. Overall, the results of previous research show that although there has been progress in the development of economic education with a focus on bank management and entrepreneurship, there are still many challenges that need to be overcome. Economic education in Indonesia needs to further strengthen practical aspects and skills by collaborating with the industrial world and the financial sector to provide real experience to students. Apart from that, integration between bank management and entrepreneurship in the economic education curriculum will be more optimal if it is supported by adequate facilities, teacher training and the use of technology. Therefore, it is recommended that the government, educational institutions and the private sector can work together to strengthen educational curricula that are more relevant to market needs and global economic challenges.